Body norms and normative bodies in Highland Guatemala. Issue 5 (2nd July 2021) - Maupin, Jonathan N.; Hackman, Joseph; Brewis, Alexandra
Abstract: Objectives: The concept of bionormalcy highlights the potential tensions between bodies defined clinically as normal or healthy, bodies that are normative (frequent) within a population, and bodies defined within a given social context as abnormal or devalued. Theories of resource scarcity predict preferences for larger bodies should deviate from what is biologically normative (i.e., most frequent) or clinically defined as healthy. Using the case of adult women in a Guatemalan community with chronically low food security, we test how food scarcity shapes individual views of smaller, larger, and clinically categorized normal bodies. Methods: Participants were 102 women from a community in the Central Highlands of Guatemala. Using the Stunkard figure scale and a word elicitation task, participants attributed positive and negative characteristics to male and female silhouettes clinically defined as underweight, normal, overweight, mildly obese, and obese. Mixed‐effects models were used to compare attribution scores for figures relative to the clinically normal silhouette. Results: Silhouettes deviating from the clinically defined normal BMI category on both sides are stigmatized to varying degrees. Food insecurity exacerbates the degree of stigma, while also relatively preferencing overweight bodies. Conclusions: In this pilot study, women exhibit a preference for body sizes that fall within the clinical normal and overweight categories and stigmatize bodies outside this range, but in distinct ways. We suggest the attachment of stigma to small and large bodies are not mirror processes, and require more detailed testing to untangle the likely complex ecological and social explanations.